When big data and Brexit collide. Issue 2 (February 2017) - Bedell-Pearce, Jack
Abstract : During the UK referendum campaign on EU membership, the Leave camp spoke ardently about the importance of protecting our sovereignty and making our own laws. Now the UK is coming out of the EU and the single market, sovereignty is top of the agenda again, for the opposite reason. Rather than solving our right to sovereignty, Brexit threatens to destabilise it. Now the UK is coming out of the EU and the single market, sovereignty is top of the agenda – but with a focus not on courts or Parliament but data. Organisations are worried about the sovereignty of their information and the onus of complying with international laws. With ever-stricter rules concerning data protection and governance, the issue of data residency is about to become more complex and dangerous, explains Jack Bedell-Pearce of 4D.